Prospective Risk Factors for Suicide Attempts in a Treated Sample of Patients with Borderline Personality Disorder. (February 2013) - Links, Paul S; Kolla, Nathan J; Guimond, Tim; McMain, Shelley
Objective: People with borderline personality disorder (BPD) are at high risk for attempting suicide. There are some data to suggest that risk factors for suicide attempts change over time. We conducted a prospective cohort study to examine risk factors for suicide attempts in a treated sample of patients with BPD. Method: One hundred eighty participants with BPD were followed over a year-long course of dialectical behaviour therapy or general psychiatric management and then for 2 more years in naturalistic follow-up. Participants were assessed for suicidal and self-injurious behaviours at baseline, every 4 months over the 1-year treatment phase, and every 6 months over a 2-year follow-up period. Participants were classified as suicide or nonsuicide attempters based on their behaviour at the end of the 1-year treatment phase and after the 2-year follow-up period. Groups were then compared on baseline clinical and demographic variables. Results: Nearly 26% of participants made a suicide attempt during the 1-year treatment phase, while 16.7% reported a suicide attempt over the 2-year follow-up period. Baseline number of suicide attempts during the 4 months prior to study and severity of childhood sexual abuse predicted suicide attempts during the treatment year. Similarly, baseline suicide attempts, severity of childhood sexual abuse, and number of hospitalizations in the 4 months prior to study entry predicted suicide attempts during the 2-year follow-up. Conclusions: Risk factors for suicide attempts in this treated sample of patients with BPD were fairly stable, largely nonmodifiable, and unrelated to psychopathology or psychosocial functioning at baseline.